Acute Alcohol Use and Suicidal Behavior: A Review of the Literature - Cherpitel, Cheryl J.; Borges, Guilherme L.G.; Wilcox, Holly C. (Alcoholism, clinical and experimental research, 2004)
: Background: Both acute and chronic use of alcohol are associated with suicidal behavior. However, the differing relationship of each component of alcohol use and possible causal mechanisms remain unclear. Methods: This article reviews and summarizes associations between acute alcohol consumption (with and without intoxication) and suicidal behavior (both completed suicide and suicide attempts) among adults 19 years and older, as presented in literature published between 1991 and 2001. Possible mechanisms and methodologic challenges for evaluating the association are also discussed. An application of a research design (the case‐crossover study) that has the potential for addressing the effects of acute alcohol use over and above usual or chronic use is presented. Results: The majority of articles reviewed were restricted to descriptive studies that documented the prevalence of suicide completers or attempters who tested positive for alcohol use. A wide range of alcohol‐positive cases were found for both completed suicide (10–69%) and suicide attempts (10–73%). Common methodologic limitations included the lack of control groups (for evaluating risk conferred by alcohol use), selection and ascertainment bias, and small sample sizes. The results of the case‐crossover pilot study indicated substantially higher risk of suicide during or shortly after use of alcohol compared with alcohol‐free periods. Conclusions: Although there is a substantial literature of published studies on acute alcohol use and suicidal behavior, the majority of studies focus on completed suicide and report prevalence estimates. Findings from such studies are subject to several possible sources of bias and have not advanced our knowledge of mechanisms in the association between acute alcohol use and suicidal behavior. The case‐crossover design may help to overcome some limitations of these studies and facilitate evaluation of associations and possible causal mechanisms by which acute alcohol use is linked to suicidal behavior.